PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM PERNAPASAN MANUSIA KELAS VIII SMP NEGERI 1 IDANOTAE T.P 2022 /2023 - Megawati Telaumbanua (TUNAS : Jurnal Pendidikan Biologi, 2023)
This study aims to determine the increase in student learning outcomes through the discovery learning model at SMP Negeri 1 Idanotae in the 2022/2023 Academic Year. This research is a class action research (CAR). The instruments used: (a) Student observation sheet, (b) Interview guide sheet, (c) Field notes, (d) Learning achievement test. The research subjects were 31 class VIII-A students of SMP Negeri 1 Idanotae. Based on the results of research that has been carried out by researchers regarding improving the quality and learning outcomes of students through the discovery learning model, it can be concluded that the learning outcomes of students have increased from cycle I where there were 71% of students who completed classically and in cycle II all students classical finish. This increase was obtained because the discovery learning model can be student-centered, where students actively discover concepts on the human respiratory system for themselves. Based on the results of this study, researchers suggest that the discovery learning model can be used to improve student learning outcomes.